2008
DOI: 10.1016/j.ibmb.2007.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Developmental expression patterns of cuticular protein genes with the R&R Consensus from Anopheles gambiae

Abstract: CPR proteins are the largest cuticular protein family in arthropods. The whole genome sequence of Anopheles gambiae revealed 156 genes that code for proteins with the R&R Consensus and named CPRs. This protein family can be divided into RR-1 and RR-2 subgroups, postulated to contribute to different regions of the cuticle. We determined the temporal expression patterns of these genes throughout post-embryonic development by means of real-time qRT-PCR. Based on expression profiles, these genes were grouped into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
99
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(107 citation statements)
references
References 43 publications
5
99
0
2
Order By: Relevance
“…Even within the same insect, they are selectively switched on or off at different developmental stages as well as in cuticles with different physical properties. Therefore, the chitin-binding cuticular proteins involved in modeling and maintaining body shape differ in identity and function according to the insect and developmental stage (Soares et al 2007;Okamoto et al 2008;Togawa et al 2008;Charles 2010), and our results show that mutation of the BmorCPR2 gene alters the overall morphology of larvae, validating its role in body-shape determination in silkworm. These findings suggest that the number, expression patterns, and functional diversification of chitin-binding cuticular proteins represent key factors in understanding the diversity of insect body shape and provide a reference to analyze the molecular basis for other body-shape mutants in silkworm.…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…Even within the same insect, they are selectively switched on or off at different developmental stages as well as in cuticles with different physical properties. Therefore, the chitin-binding cuticular proteins involved in modeling and maintaining body shape differ in identity and function according to the insect and developmental stage (Soares et al 2007;Okamoto et al 2008;Togawa et al 2008;Charles 2010), and our results show that mutation of the BmorCPR2 gene alters the overall morphology of larvae, validating its role in body-shape determination in silkworm. These findings suggest that the number, expression patterns, and functional diversification of chitin-binding cuticular proteins represent key factors in understanding the diversity of insect body shape and provide a reference to analyze the molecular basis for other body-shape mutants in silkworm.…”
Section: Resultssupporting
confidence: 61%
“…We analyzed the upstream and downstream sequences of S0 in the silkworm database. Close to the S0 marker, we observed two predicted gene models encoding RR1-type chitin-binding cuticular proteins that play an important role in construction of the soft insect cuticle (Andersen et al 1995(Andersen et al , 2011Togawa et al 2008;Moussian 2010;Willis 2010) (Figure 2A-iii). Full-length cDNA of BGIBMGA005278 (BmorCPR3) was not different in wild type and stony, and the gene expression patterns were relatively similar (Figure 2A-v, and Figure S2).…”
Section: The Stony Locus Encodes Bmorcpr2mentioning
confidence: 99%
See 1 more Smart Citation
“…Transcriptional regulation of CP gene expression appears to be regulated by developmental and hormonal cues (Ali et al, 2013;Charles, 2010). Togawa et al (2008) analyzed the temporal expression patterns of 152 CPR genes in A. gambiae by using real-time PCR. These were grouped into 21 clusters based on expression profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Togawa analyzed expression patterns from precisely timed, relative to ecdysis, first-instar larvae to newly eclosed adults, 19 stages in all. This analysis revealed that the genes in sequence clusters shared temporal patterns of expression and that their expression levels were high (41). We suspect that the amplification of these genes reflects the need for massive protein synthesis to accompany the very rapid development of An.…”
Section: Wwwannualreviewsorg • Arthropod Proteomics and Genomicsmentioning
confidence: 92%